66. Cannabinoids may influence motor cortical excitability: A double-blind neurophysiological study. Issue 4 (April 2016) - Cambieri, C.; Ceccanti, M.; Fionda, L.; Tartaglia, G.; Cicchinelli, A.; Frasca, V.; Onesti, E.; Gori, M.C.; Inghilleri, M.
Abstract : Endogenously released cannabinoids (CBD) are involved in several neuronal processes; they act via two receptors subtypes: cannabinoid receptor type 1 (CB1) – expressed in central nervous system neurons – and cannabinoid receptor type 2 (CB2) – expressed in immune system cells, microglia and neuronal progenitor cells. Δ9-tetrahydrocannabinol (THC), the most important active metabolite of cannabidiol, shows a partial agonist activity on cannabinoid receptors. The aim of this study was to evaluate the effect of the dronabinol on the Resting Motor Threshold (RMT) registered at the first dorsal interosseous (FDI), on the motor evoked potential (MEP) amplitude, and on the latency and duration of the Cortical Silent Period (CoSP) in 13 healthy subjects. All subjects underwent two separate sessions: one with dronabinol (5 mg) and the other with bromazepam (1.5 mg) used as control-drug. Healthy subjects were tested immediately before and one hour after the drug administration. No significant differences were found on MEP amplitude and CoSP values between the two groups. RMT was significantly reduced in subjects treated with dronabinol compared to those treated with bromazepam ( p < 0.05). Previous studies indicate that – even after a single exposure to THC – prolonged cortical hyperexcitability occurs, with an increased susceptibility to convulsions. Recent studies show that chronic cannabis use is associated with a reduction in cortical inhibition, potentially related to the activity of GABA-A receptors. Our preliminary data suggest that further research is needed to delucidate the effects of CBD on cortical excitability and to better understand the mechanisms underlying CBD's involvement in epilepsy.